2019
DOI: 10.1021/acsami.8b18497
|View full text |Cite
|
Sign up to set email alerts
|

An Enzyme-Free “ON-OFF” Electrochemiluminescence Biosensor for Ultrasensitive Detection of PML/RARα based on Target-Switched DNA Nanotweezer

Abstract: Herein, an enzyme-free "ON-OFF" electrochemiluminescence (ECL) biosensor for ultrasensitive detection of fusion gene PML/RARα is constructed based on a simple target-switched DNA nanotweezer as hemin concentration controller. In this biosensor, the hemin concentration is primarily controlled by the conversion of "opened-closed" DNA nanotweezers and low concentration hemin is first used as electrochemically regenerable enhancer. In the absence of the target, the nanotweezers are in an opened state which lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 33 publications
(46 reference statements)
0
23
0
Order By: Relevance
“…By modifying fluorescent molecules at specific tweezer arms, fluorescence resonance energy transfer can be clearly observed when operating the DNA tweezers. On the basis of this finding, a series of biosensing applications including microRNA, gene and protein analysis, and pH monitoring have been demonstrated. Interestingly, a DNA tweezer was reported to precisely tune the distance between the enzyme and cofactor which is modified at tweezer arms, leading to an enzyme nanoreactor to regulate the biofunction of the enzyme .…”
mentioning
confidence: 98%
“…By modifying fluorescent molecules at specific tweezer arms, fluorescence resonance energy transfer can be clearly observed when operating the DNA tweezers. On the basis of this finding, a series of biosensing applications including microRNA, gene and protein analysis, and pH monitoring have been demonstrated. Interestingly, a DNA tweezer was reported to precisely tune the distance between the enzyme and cofactor which is modified at tweezer arms, leading to an enzyme nanoreactor to regulate the biofunction of the enzyme .…”
mentioning
confidence: 98%
“…(25)(26)(27)(28) Also, in addition to a colorimetric method, other methods such as electrochemical detection with split Gq-based DNA-NTs were reported. (19)(20)(21) Therefore, by the combination of these methods, it is expected that split Gq-based DNA-BNA chimera NTs will be applicable to the development of POCT devices for the detection of a wide variety of nucleic acids as target recognition and signal generation elements.…”
Section: Discussionmentioning
confidence: 99%
“…(10) Because of a simple structure and principle, the split Gq-based DNA-NTs and their derivatives have also been utilized by other research groups for the detection of a protein (18) and applied to the electrochemical detection of target nucleic acids. (19)(20)(21) However, the target recognition ability of split Gq-based DNA-NTs has not been precisely investigated yet. Specifically, it is unclear whether they can recognize short nucleic acids with a single-base mismatch.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the above method Bian et al reported a DNA nanotweezer-based platform for detecting the fusion gene promyelocytic leukemia, retinoic acid receptor alpha (PML/RARα). 98 PML/RARα is a biomarker for acute promyelocytic leukemia, and the sensitive detection of PML/RARα is crucial for the early diagnosis of leukemia. 99,100 The biosensor is based on the ECL response by combining DTs with G-quadruplexes.…”
Section: ■ Application Of Dts In Biosensingmentioning
confidence: 99%